Adaptive nematic liquid crystal lens array with resistive layer. Issue 4 (15th March 2020) - Chu, Fan; Tian, Li-Lan; Li, Rui; Gu, Xiao-Qing; Zhou, Xiang-Yu; Wang, Di; Wang, Qiong-Hua
ABSTRACT: We propose an adaptive nematic liquid crystal (LC) lens array using a dielectric layer with low dielectric constant as resistive layer. With the resistive layer and periodic-arranged iridium tin oxide (ITO) electrodes, the vertical electric field across the LC layer varies linearly over the lens aperture is obtained in the voltage-on state. As a result, a centrosymmetric gradient refractive index profile within the LC layer is generated, which causes the focusing behaviour. As a result of the optimisation, a thin cell gap which greatly reduces the switching time of the LC lens array can be achieved in our design. The main advantages of the proposed LC lens array are in the comparatively low operating voltage, the flat substrate surface, the simple electrodes, and the uniform LC cell gap. The simulation results show that the focal length of the LC lens array can be tuned continuously from infinity to 3.99 mm by changing the applied voltage. Graphical abstract: